In the Aftermath of Welfare “Reform” - Tourigny, Sylvie C. (Social justice, 2001)
The writers introduce an issue that strives to evaluate the fallout in the U.S. of the Personal Responsibility and Work Opportunity Reconciliation Act of 1996 (PRWORA). Although PRWORA has resulted in falling welfare rolls and an era of “personal responsibility,” the popular press and ethnographic accounts increasingly challenge that view, highlighting the staggering human costs among those who remain in the ideological cross fire.